The Summer Swap - Morgan, Sarah, (Romance fiction writer) (Toronto, Ontario : Canary Street Press, 2024)
Cecilia Lapthorne always vowed she$1 (Bd never go back to Dune Cottage. So no one is more surprised than Cecilia to find herself escaping her seventy-fifth birthday party to return to the remote Cape Cod cottage$1 (Ba place filled with memories. Some are good$1 (Bespecially memories of the early days with her husband, volatile artist Cameron. But then there are the memories she has revealed to no one. After dropping out of medical school, aspiring artist Lily is cleaning houses on the Cape to get by, guilt-ridden for disappointing her parents. Unoccupied for years, Dune Cottage seems the perfect place to hide away and lick her wounds$1 (Buntil Cecilia unexpectedly arrives. Despite an awkward beginning, Lily accepts Cecilia$1 (Bs invitation to stay on as her guest, and a flicker of kinship ignites. Then Todd, Cecilia$1 (Bs grandson$1 (Band Lily$1 (Bs unrequited crush$1 (Bshows up, sending a shock wave through their unlikely friendship. Will Lily find the courage to live the life she wants? Can Cecilia finally let go of the past to find a new future? Because as surely as the tide erases past footprints, this summer is offering both Cecilia and Lily the chance to swap old dreams for new$1! =(B.s
new book 2024 summer.
Keywords: Cottages -- Fiction; Female friendship -- Fiction; Memory -- Fiction; Older women -- Fiction; Squatters -- Fiction; Cape Cod (Mass.) -- Fiction